Physics of Magnetopause Reconnection: A Study of the Combined Effects of Density Asymmetry, Velocity Shear, and Guide Field - Kentaro G. Tanaka; Masaki Fujimoto; Iku Shinohara (International Journal of Geophysics)
Magnetopause reconnection would be characterized by the density jump across the current sheet, the flow shear across the boundary, and nonzero guide field. While effects of each of these elements have been studied, the effects arising from the combination of these are still unexplored. Two-dimensional full-particle simulations show that the combination of shear flow and/or guide field with density asymmetry induces the sliding motion of the X-line along the magnetopause. The direction of the X-line motion is controlled either by the ion flow at the X-line when the shear flow effects dominate or by the electron flow at the X-line when the guide field effects dominate. The shear flow effects and the guide field effects may counteract each other in determining the direction of the X-line motion and, in the close proximity of the subsolar region where the flow is slow, the X-line motion can be opposite to the flow direction.